Whatsapp addiction: assessing pattern of Whatsapp usage and its impact on medical students at U.P.U.M.S., Saifai, Etawah, India - Singh, Nishant; Singh, Naresh Pal; Kharya, Pradip; Shukla, Sushil; Singh, Vaibhav; Raj Singh, Deepali (International Journal Of Community Medicine And Public Health, 2019)
Background: Mobile phone addiction is the compulsive use of a mobile phone by youth across the world. A new kind of health disorder in this category among smartphone users is “Whatsapp addiction”. Medical students are also affected by this high smartphone engagement. Methods: It was a cross sectional study, which was conducted among M.B.B.S. students of Uttar Pradesh University of Medical Science, Saifai, Etawah, India. All the M.B.S.S. students willing to participate and present at the time of the study included. The data was collected by using pre designed semi-structured questionnaire. Proforma included socio demographic profile, usage pattern and its impact. Results: This study revealed that most of the participants are males (60.75%). Approximately 54% participants felt that their concentration has been reduced due to Whatsapp use, 43.6% participants experienced strain/diminution of vision and 38.4% participants perceived that their physical activity has been reduced due to Whatsapp use. Conclusions: Whatsapp overuse affects the study duration, concentration, physical activity and sleep.